Community transmission of a virus: a global pandemic overview - N., Ravindra B.; Das, Lipika; C., Darshan J.; Ghosh, Sayantan; Kurian, Berlin P.; Paul, Prolay; Reddy, Meghana A.; B. P., Satish Kumar (International Journal Of Community Medicine And Public Health, 2021)
The word ‘pandemic’ was originally a derivative from two Greek words “pan” referring “all” and “demos” “people”. “An epidemic arising over a very diverse area, crossing the global margins, and typically affecting a huge number of people” is defined as a pandemic. Therefore pandemics are recognized by their topographical scale instead of severity of ailments. Even though the term “pandemic” has not been clearly defined, wide geographic extension, disease movement, novelty, severity, high attack rates and explosiveness, minimal population immunity, infectiousness and contagiousness can be considered as some of the key features of this term. Till today, globe has encountered several notable pandemics caused by virus such as Spanish flu, acquired immune deficiency syndrome (HIV/AIDS), smallpox, SARS, Ebola and Nipah disease whose causative organisms are H1N1, human immunodeficiency virus (HIV), Variola virus, DEN-1/DEN2/DEN3/DEN4, coronavirus, Ebola virus (Zaire/Sudan/Tai/Cote D’ivoire), and Nipah virus (NiV) respectively. This review includes detailed data regarding various viral pandemics. Analyzing the history, clinical manifestation, pathogenesis, management and precautions of several viral pandemics which will promote and spread the awareness among the public as well as the healthcare system.